Economic Empowerment Strategy for Coastal Communities of Lakkang Island, Tallo District, Makassar City - Ruslan, Muh. Reza Hidayat; Herman H; Novayanti Sopia Rukmana; Andi Anugrah Mahyuddin (Universitas Negeri Makassar, 2025)
This study aims to identify and describe the process of the Coastal Community Economic Empowerment Strategy. This type of research is descriptive qualitative. Data collection techniques are done through observation, interviews, and documentation. Data analysis techniques include data collection, reduction, presentation, and conclusion drawing. The results of the Research on the Economic Empowerment Strategy of the Coastal Community of Lakkang Island, Tallo District, Makassar City show that the sub-variables (1) standards and targets are good; this can be seen from the strategic steps to optimize the potential of existing natural and human resources. (2) adequate resources; this can be seen from the active involvement of the community in managing natural resources, especially fisheries and tourism, and maintaining existing sustainability. (3) good local leadership can be seen from the good cooperation and coordination between all elements on the island of Lakkang, namely local farmer and fishermen groups, local tourism entrepreneur groups, community or traditional leaders, village government, and related parties. (4) Equitable partnerships with stakeholders have not worked well, as evidenced by the lack of coordination between institutions and stakeholders, with empowerment programs often not well integrated. (5) the use of local technology and data is also not good, as seen from access to modern technology, for example, the use of satellite-based monitoring systems in monitoring fish stocks or more sophisticated processing tools that can help improve product quality. In conclusion, the economic empowerment strategy of the coastal community of Lakkang Island has generally been running well, especially in terms of standards, such as the strategy of optimizing the potential of natural resources and then adequate resources with active involvement from the local community, and coordination between all elements of the community on Lakkang Island. However, there are challenges in using modern technology that are not yet adequate due to limitations and technology training assistance that hampers the economic empowerment strategy of coastal communities on Lakkang Island.